Poverty and Social Impact Assessment of Systematic Registration on Rural Romania - World Bank Group (World Bank, Washington, DC, 2016)
The objective of this Poverty and Social Impact Analysis (PSIA) is to assess the impact of systematic registration on vulnerable individuals, in general, and Roma, in particular. Specifically, this PSIA focuses on the systematic registration approach piloted under the Complementing EU Support for Agricultural Restructuring (CESAR, 2009 - 2013) Project, which was supported by the World Bank. The World Bank involvement in the sector dates back to 1998 and the General Cadastre and Land Registration Project that supported the establishment of an efficient system for securing and trading land titles. The overall economic impact of the National Program was estimated to be extremely positive with eightfold return to the investment. However, it was also recognized that specific measures needed to be adopted to ensure that the rights of vulnerable groups (especially those of rural Roma communities) would be duly registered and to monitor the impact of real property rights registration to vulnerable groups and individuals. The findings of this PSIA are directly relevant to the EU financed Rural Land Registration Program design, which has adopted the vulnerability mapping and social monitoring approach, and seeks to improve it. Early PSIA results have also contributed to the dozens of systematic registration contracts signed under the National Program, which are registration fee financed. Contractors are required to pay particular attention to the vulnerable groups. This PSIA was conducted by the Romanian firm Metro Media Transilvania from 2014-2015. It is largely based on a field survey carried out in February 2015 by the same firm in 6 UATs, 4 or which were targeted by CESAR. The sample included 480 households, comprising 360 households living in Roma settlements, and 120 vulnerable people living outside of these settlements such as analphabets, elderlies, convicts, and widows. The results of this survey are anecdotal; however, they provide valuable information on the participation of vulnerable groups in CESAR and highlight possible improvements in the systematic land registration process.